The challenges and benefits of employing a mobile research fellow to facilitate team work on a large, interdisciplinary, multi-sited project - Sugden, Fraser; Punch, S. (SAGE Publications, 2014)
Over the last few years research funding has increasingly moved in favour of large, multipartner, interdisciplinary and multi-site research projects. This article explores the benefits and challenges of employing a full-time research fellow to work across multiple field sites, with all the local research teams, on an international, interdisciplinary project. The article shows how such a ‘floating’ research fellow can play a valuable role in facilitating communication between research teams and project leaders, as well as in building capacity and introducing disciplinary specific skills. It also highlights some key challenges, including problems of language and translation, and the complex power relations within which such a researcher is inevitably embedded. This article contributes to the development of strategies for collaborative projects to facilitate coordination between research teams. It is based on a five-site, cross-cultural project, involving nine partners with a mixture of natural and social science backgrounds, researching aquatic resource use, rural livelihoods, work and education in China, Vietnam and India.